Anionic three-dimensional porous aromatic framework for fast Li-ion conduction - Seongsoo, Lee; Jeong, Ji won; Moon, J.; Kim, M.; Amarasinghe, K.V.L.; Chung, Kyung Yoon; Lim, Hee Dae; Whang, D. (Elsevier BV, 2021)
Solid polymer electrolytes (SPEs) have been received significant attention due to their inherent advantages of high safety and high electrochemical stability as fast Li-ion conductors. However, conventional SPEs of dual-ion conductors (i.e., conducting both anions and cations) are prone to induce concentration polarization and thus decrease in ionic conductivities, which remains a significant hurdle for their practical applications. Here, we propose a new host of porous aromatic frameworks (PAFs) as a promising single Li-ion conducting SPEs. PAF1 is one of the promising types for crystalline polymers with the integration of aromatic organic building units into a 3-dimensional framework, having plenty of voids space inside. By covalently tethering the sulfonate on aromatic groups, anions are immobilized onto the frameworks, and the exchanging process of protons with Li-ions makes it perform as a fast Li-ionic conductor. Consequently, Li sulfonated PAF1 (denoted as Li-SPAF1) shows superior ion-conducting properties of 0.102 mS cm？1 at room temperature with the activation energy of 0.21 eV. It is demonstrated that the aromatic groups have high chemical and thermal stabilities, even stable with Li metal, which is advantageous for delivering stable electrochemical performances. Also, the structure and conduction mechanism are theoretically investigated by using density functional theory calculations. ？ 2021